A Novel Intronic Mutation in MBD5 Results in Autosomal Dominant Intellectual Disability Type 1 due to Abnormal Splicing - Heng Jiang; Jingjing Mou; Qiwei Zhao; Long Ding; Yu Wang; Xiaohong Guo; Guohua Yang (Molecular Genetics & Genomic Medicine, 2025)
ABSTRACT Background We identified a novel variant in MBD5 located within intron 6: c.114‐13A>G (NM_018328.5) in a family with a patient presenting intellectual disability. This variant is hypothesized to be the etiological agent underlying the patient's condition. Methods We conducted an analysis of mRNA splicing within the patient and their relatives' blood samples via reverse transcription polymerase chain reaction (RT‐PCR) to assess intronic mRNA splicing. Additionally, we employed a minigene vector construction approach to verify in vitro the splicing of mRNA containing the mutated fragment. Protein structure prediction analysis of the aberrant mRNA was performed using PyMOL software. Results The patient harbors a novel mutation in the MBD5 gene: c.114‐13A>G. Analysis of the patient's blood sample revealed the presence of aberrantly sized mRNA molecules. Utilizing a minigene approach, we discovered that this mutation results in the generation of two types of abnormally sized mRNAs. The first type of abnormal splicing leads to a 12‐base pair retention at the 3′ end of intron 6, and the second type of abnormal splicing causes exon 7 skipping. Conclusion In accordance with the “Standards and Guidelines for the Interpretation of Sequence Variants” established by the American College of Medical Genetics and Genomics (ACMG), the novel mutation c.114‐13A>G in the MBD5 gene meets the criteria for PS2 (the variant is de novo and not inherited from either parent) and PS3 (the variant affects mRNA splicing, resulting in aberrant transcripts). We propose that the c.114‐13A>G variant, located within intron 6 of the MBD5 gene, is pathogenic. This discovery not only expands the repository of pathogenic variants for MBD5 but also provides additional insights into intronic mutations of the MBD5 gene, thereby offering significant information for the genetic diagnosis of Autosomal Dominant Intellectual Disability Type 1.